How Influencer Doctors Use Social Media? A Content Analysis on Marketing Communications, Patient Privacy and Ethics - Güldane Zengin (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Medical doctors have a high level of source credibility and a reputable profession. Some of them also share their expertise on social media. This led to so some doctors gaining thousands and millions of followers and becoming “influencer doctors”. Every bit of information that a medical doctor share is important for the followers. Influencers are content creators with a large social media following, and this makes them appealing for brands. Collaborations with brands are common for influencers. When it comes to influencer doctors, who have more credibility due to their profession, it can be said that they have an advantage over ordinary influencers, a power to drive their followers’ decisions. However, it is prohibited by law and regulations for medical doctors to advertise in any medium. Thus, in this study it was aimed to reveal medical doctors’ compliance with Turkish Medical Association’s rules on social media. A content analysis on 13 medical doctors’ Instagram stories was conducted. Each doctor has more than 500.000 followers and they shared a total of 565 stories. According to the findings, product promotions are most common content for the stories of these influencer doctors. They also share stories that showcase or promote their services; that contain patient information in which more than half are privacy breaches; and none included a disclosure on patient permission to reveal such information.